2016
DOI: 10.3892/mmr.2016.5261
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role and reduced expression of FOXJ2 in human hepatocellular carcinoma

Abstract: The current study aimed to investigate the potential role of the FOXJ2 (forkhead box J2) protein in the pathology of hepatocellular carcinoma (HCC). Western blotting was performed to determine the expression levels of FOXJ2 in HCC tissues and HCC cells. Specimens from 110 patients with HCC undergoing hepatic resection were evaluated for FOXJ2 expression using an immunohistochemical assay. The correlation between FOXJ2 expression and clinicopathological factors of the patients was determined by statistical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Among the predicted transcription factors, FOXJ2 was the first transcriptional factor that might regulate PGM1 expression and was also reported to suppress tumor growth. FOXJ2 is a member of the forkhead transcription factor family [ 16 ] and was down-regulated in HCC and extrahepatic cholangiocarcinoma [ 17 , 18 ]. We therefore tested whether FOXJ2 regulates PGM1 expression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the predicted transcription factors, FOXJ2 was the first transcriptional factor that might regulate PGM1 expression and was also reported to suppress tumor growth. FOXJ2 is a member of the forkhead transcription factor family [ 16 ] and was down-regulated in HCC and extrahepatic cholangiocarcinoma [ 17 , 18 ]. We therefore tested whether FOXJ2 regulates PGM1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…As described in Fig 1E and 1F , decreased PGM1 expression correlated with poor prognosis of HCC patients. FOXJ2 expression has also been suggested to correlate with poor prognosis of HCC patients [ 18 ]. To determine prognostic potential of integrated analyses of PGM1 and FOXJ2 expression, we divided 272 HCC patients into 2 groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 14 ] In addition, FOXJ2 could also inhibit the proliferation of human hepatocellular carcinoma cells, and reduced expression of FOXJ2 was significantly associated with the poor prognosis of patients with human hepatocellular carcinoma. [ 20 ] The present study revealed that low FOXJ2 expression was associated with advanced FIGO stage by assessing 151 epithelial ovarian cancer cases. Besides, FOXJ2 expression was significantly different regarding treatment approaches.…”
Section: Discussionmentioning
confidence: 75%
“…[ 13 17 ] FOXJ2 was shown to positively regulate cell cycle progression and induce tumorigenesis. [ 18 , 19 ] However, FOXJ2 was described as a tumor suppressor in liver cancer, [ 20 ] indicating that its exact function in cancer deserves further investigation.…”
Section: Introductionmentioning
confidence: 99%